BRAND NAME AND PRICE PERCEPTION AS CORRELATES OF ONLINE PURCHASE INTENTIONS AMONG UNDERGRADUATES OF NNAMDI AZIKIWE UNIVERSITY, AWKA - Ezeanya, Ifenna D.; Ebom, Chinwendu Jennifer; Mabia, Chidozie Emmanuel; Anene, Kingsley O. (African Journal of Social and Behavioural Sciences, 2024)
This study examined brand name and price as correlates of online purchase intentions among undergraduates at Nnamdi Azikiwe University, Awka. A total of 200 participants consisting of 108 females and 92 males participated in this study. The participants ranged from 18 to 29 years, with a mean age of 21.30 years and standard deviation of 2.63 years. Three self-report survey instruments were utilized for the study: the brand name scale by Yee and Yahyah (2008), the price perception scale by Sanchez et al., (2006) and the online purchase intentions by Zarrad and Dababi (2012). A correlational design was adopted for the study, while the Pearson product-moment correlation coefficient was used for data analysis. Two hypotheses were tested and the results showed that both brand name and perceived price had a positive significant relationship with online purchase intentions. Based on the findings of this study, the researchers, therefore, recommend that marketers and business owners to focus on competitive pricing strategies.